تنمية المساواة بين الجنسين فى أحكام الأسرة بإندونيسيا: قضية الولي والشاهدين فى النكاح - Ahmad Rajafi (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
There are so many problems that can be found in Islamic Family Law viewed from modernapproach especially gender equality. Starting from the rule of marriage guardian that controlled bymen, inheritance dominated by men, and also all the provisions concerning the witnesses whichweakens the existence of women. In Indonesia context it, is important to analyze the problem ofguardian and witness of marriage through the maqashid asy-syari’ah and will find the solution wherethe guardian of marriage is the primary element in order to guard of honor and about witness ofmarriage as a secondary element that has the function as the main purpose of marriage. Based onthat classification, it was found that the primary element about the guardian and the secondaryelement about witness of marriage, it led significant difference between the Arab and Indonesiacontext. Therefore, reforms are needed in the Islamic Family Law through the cultural approachso it can be responsive in Indonesia. In the Arab culture is patriarchal (patrilineal) master, while inIndonesia there are multi kinships complex such as patrilineal, matrilineal and bilateral, it impliesthe need reformations that bring the solution accordance with the local wisdom of Indonesia forthe instance the implementation of gender equality openly.